2013
DOI: 10.1055/s-0033-1344548
|View full text |Cite
|
Sign up to set email alerts
|

Post-polypectomy colonoscopy surveillance: European Society of Gastrointestinal Endoscopy (ESGE) Guideline

Abstract: This Guideline is an official statement of the European Society of Gastrointestinal Endoscopy (ESGE). The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system was adopted to define the strength of recommendations and the quality of evidence. Main recommendations: The following recommendations for post-polypectomy endoscopic surveillance should be applied only after a high quality baseline colonoscopy with complete removal of all detected neoplastic lesions. 1 In the low risk grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
514
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 505 publications
(529 citation statements)
references
References 128 publications
6
514
0
9
Order By: Relevance
“…Finally, it is also important to note that, according to most current guidelines, with the use of an HD+i-SCAN colonoscope, in our study, a higher proportion of patients (although not statistically significant) would be classified as having high-risk-adenoma, in which the recommended post-polypectomy surveillance interval for an effective prevention of CRC is shortened to 3 years (30,31) (Table II and Fig. 2).…”
Section: Discussionmentioning
confidence: 54%
“…Finally, it is also important to note that, according to most current guidelines, with the use of an HD+i-SCAN colonoscope, in our study, a higher proportion of patients (although not statistically significant) would be classified as having high-risk-adenoma, in which the recommended post-polypectomy surveillance interval for an effective prevention of CRC is shortened to 3 years (30,31) (Table II and Fig. 2).…”
Section: Discussionmentioning
confidence: 54%
“…Adenomas were defined as advanced when they were 10 mm or larger or had villous architecture, high-grade dysplasia, or intramucosal carcinoma, or when three or more adenomas were found. [1][2][3] Advanced adenomas at baseline were classified as intermediate risk or high risk according to the European Guidelines of Surveillance.…”
Section: Variablesmentioning
confidence: 99%
“…The indication for and timing of the colonoscopies are based on a risk estimation, and different guidelines recommend follow-up schedules depending on findings at baseline, specifically the size and number of adenomas. [1][2][3] However, the evidence supporting these recommendations is of low to moderate quality. 2 On the other hand, colonoscopy quality varies considerably among endoscopists, with important variations in fulfillment of quality indicators, such as adenoma detection rate (ADR) or adenomas per colonoscopy rate (APCR).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have suggested that basal colonoscopy findings stratify adenomas into low-or high-risk (i.e. adenoma ≥10 mm, villous adenoma, adenoma with high-grade dysplasia, or invasive cancer) groups for recurrent adenomas during surveillance colonoscopy (3,4). CRC arises from both genetic and environmental factors and their interaction.…”
Section: Introductionmentioning
confidence: 99%